STANDARDIZATION OF SPECIFIC AND NON-SPECIFIC PARAMETERS, PHYTOCHEMICAL ANALYSIS, AND KLT PROFILE OF JACKFRUIT SEED EXTRACT (ARTOCARPUS HETEROPHYLLUS LAM) - Wiwit Zuriati Uno; Aprilia Hulopi; Fadhilah Nur Rahma Bau; Hariyanto Suronoto; Nazwa Amalia Lantapa; Sasya Ramadhani Usman (JIMR : Journal Of International Multidisciplinary Research, 2025)
This study aimed to determine the specific parameters, non-specific parameters, phytochemical screening results, and TLC profile of jackfruit seed extract. The evaluations included organoleptic assessment, moisture content, total ash content, microbial contaminat ion, phytochemical identification, and TLC analysis using n-hexane: ethyl acetate eluents. The results showed that the extract was viscous, yellow-brown, and had a characteristic aroma; the moisture content was 6% and the total ash content was 2.85%, both meeting the quality requirements. Microbial contamination indicated acceptable values with total plate count at dilutions 10?²–10?³ and yeast-mold count at dilutions 10?¹–10?², remaining below the maximum limits. Phytochemic al screening identified the presence of alkaloids and steroids/terpen oids, while flavonoids, tannins, and saponins were not detected. TLC profiling produced several Rf values indicating the dominance of non-polar to semi-polar compounds. These findings demonstrate that jack fruit seed extract meets physical, chemical, and microbiological qua lity standards and presents a consistent chemical profile, supporting its potential for use as a raw material in herbal product development.